Brazil’s first free-mating laboratory colony of Nyssorhynchus darlingi - Araujo, Maisa da Silva; Andrade, Alice Oliveira; Santos, Najara Akira Costa dos; Pereira, Dhélio Batista; Costa, Glaucilene da Silva; Paulo, Paula Frassinetti Medeiros de; Rios, Carlos Tong; Moreno, Marta; Pereira-da-Silva, Luiz Hidelbrando; Medeiros, Jansen Fernandes de (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
The lack of highly-productive Nyssorhynchus darlingi laboratory colonies limits some studies. We report the first well-established laboratory colony of Ny. darlingi in Brazil. Mosquitoes were collected from Porto Velho and were reared at the Laboratory of Fiocruz/RO. After induced mating by light stimulation in the F1 to F6, the subsequent generations were free mating. Larvae were reared in distilled water and fed daily until pupation. In 11 generations, the colony produced a high number of pupae after the F5 generation. These results demonstrate the potential for permanently establishing Ny. darlingi colonies for research purposes in Brazil.